Alterations in the Survivability and Gross Morphology of Chick Embryos Following Exposure to Glucose - Minhas, Ruqqia Shafi; Syed, HamdbinteShahab; Rafi, Aisha; Saleem, Anber; Rashid, Nadia; Akhtar, Lubna; Yasmeen, Maria (ADVANCES IN BASIC MEDICAL SCIENCES, 2020)
Objective: To evaluate the effects of administration of glucose on survivability and gross developmental malformations of the chick embryos in comparison with age matched controls. Methodology: This was an experimental study carried out at Anatomy Department, Regional Centre, College of Physicians and Surgeons Pakistan, Islamabad. Glucose (5% weight/volume solution) was injected in the albumen of fertilized eggs before incubation in experimental group B (n=60) while normal saline was given in control group A (n=60). Both groups (A and B) were compared for survivability and gross developmental malformations. Eggs in the subgroups A1(n=30) and B1(n=30) were opened on day 10 of incubation while subgroups A2(n=30) and B2(n=30) were opened at hatching or day 22. Results: In the glucose exposed group B1, 22 (73.3%) chicks were alive while 8 (26.6%) were dead. Upon hatching, 23 (76.6%) of the chicks belonging to the experimental group B2 survived, while 23.3% died. In control group 29 (96.6%) embryos survived in A1 while 1(3.3%) was dead. All embryos from subgroup A2 survived. The difference of survivability between the experimental and the control groups was significant at the embryonic stage (p=0.005 as well as at the hatching stage (p=0.013).The experimental animals showed a number of gross deformities with failure of closure of neural tube and anterior abdominal wall. There was herniation of brain, thoracic and abdominal viscera. Some experimental animals demonstrated absent lower limbs and others were unable to stand and walk properly. None of these anomalies were shown by embryo of the control group. Conclusion: Glucose exposed embryos demonstrated decreased survivability and gross developmental malformations. Key words: Glucose, chick embryos, malformations, diabetes